2017
DOI: 10.7704/kjhugr.2017.17.4.200
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study ofHelicobacter pyloriEradication Using a Polymerase Chain Reaction-based Test for Clarithromycin Resistance

Abstract: Background/Aims: Clarithromycin resistance is one of the main predictors of eradication treatment failures in Helicobacter pylori infections. The aim of this study was to investigate the ideal eradication rate of more than 90% of tailored therapies using a polymerase chain reaction (PCR)-based test for clarithromycin resistance in patients with peptic ulcer disease. In addition, we evaluated the possibility of sequential therapies for infections due to clarithromycin-resistant strains. Materials and Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
(40 reference statements)
3
6
0
Order By: Relevance
“…However, there remained some limitations on PCR‐based tailored therapy as a primary H pylori eradication therapy. Although the tailored therapy showed an excellent eradication rate, the group with CLA‐R or Dual‐R strains showed relatively low eradication rates (70%‐80%), whereas those with CLA‐S strains showed higher eradication rates (>90%), as reported in previous studies . Our results also showed that the CLA‐R group had low eradication ratio (ITT/PP 77.8%/87.5%) compared with the NR group (ITT, 94.0% and PP, 94.0%).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…However, there remained some limitations on PCR‐based tailored therapy as a primary H pylori eradication therapy. Although the tailored therapy showed an excellent eradication rate, the group with CLA‐R or Dual‐R strains showed relatively low eradication rates (70%‐80%), whereas those with CLA‐S strains showed higher eradication rates (>90%), as reported in previous studies . Our results also showed that the CLA‐R group had low eradication ratio (ITT/PP 77.8%/87.5%) compared with the NR group (ITT, 94.0% and PP, 94.0%).…”
Section: Discussionsupporting
confidence: 82%
“…which was consistent with those reported in previous studies and meta-analysis. 9,10,15,20,21 Currently, the most widely used empirical H pylori eradication therapy is the CLA-based standard triple therapy, which includes the use of two antibiotics (amoxicillin and clarithromycin) together with PPI. 2 However, the existing standard triple therapy reported unsatisfactory eradication success rate, which was influenced by several factors such as antibiotic susceptibility, insufficient inhibition of acid, bacterial genotypes that reduce virulence, and compliance.…”
Section: Culture and Mic Resultsmentioning
confidence: 99%
See 3 more Smart Citations